Labor market intermediaries and effectiveness of job search methods during the economic crisis - Alva, Kenedy; Escot, Lorenzo; Fernández Cornejo, José Andrés; Cáceres Ruiz, Juan Ignacio (Cuadernos de Relaciones Laborales, 2017)
The high unemployment rates experienced by the Spanish economy since the economic crisis justify that much of the public policies have focused on improving the chances of reemployment of unemployed workers. In this regard, effective intermediation between labor supply and demand is essential to reduce time in job search. This paper presents an analysis of the various intermediaries and mechanisms of job search during the economic crisis. We quantify the most used methods by job seekers, and which of these mechanisms were more effective in finding a job. We will use data of a survey conducted in the Community of Madrid in 2013 to both unemployed job seekers and workers that had found their jobs recently. According to this survey, despite that specific internet portals for job search were the most used, on the contrary, personal and professional direct contact methods were the most effective to find a job.
Keywords: unemployment; labor market intermediaries; job search; job search methods; active employment policies; employment guidance.